Conceptualization of a holistic brand image measure for fashion-related brands. Issue 4 (8th June 2015) - Cho, Eunjoo; Fiore, Ann Marie
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to conceptualize the holistic nature of brand image for fashion-related products and to complete the initial stage of scale development, determining content validity, for a new brand image measure. Design/methodology/approach – The conceptualization of brand image was based on a review of academic and industry literature and analysis of qualitative data from 11 in-depth interviews. To help assess content validity, four trained judges assessed the face validity of the initial 140 items generated; 137 scale items were retained. Findings – Analysis of the interview data revealed that cognitive (mystery), emotional (intimacy) and sensory (sensuality) dimensions were important for brand image of fashion-related products. The results aligned with major themes proposed in the literature, but one additional theme (self-congruity) was uncovered. These findings support content validity of the brand image scale items. Research limitations/implications – The interviews were limited to female consumers in the Midwestern USA. The present study expands the existing brand image concept by identifying its multi-dimensional nature including sensory associations. Theoretically, an expanded brand image measure increases its explanatory power in empirical studies. In terms of practical implications, fostering cognitive, emotional and sensory dimensions is essential for creating an effective fashion-related brand image, which can enhance brand equity. Originality/value – Past brand image scales have emphasized cognitive and emotional dimensions. The new scale items represent a more holistic measure of brand image, as they include a comprehensive sensory dimension. It will be the first brand image scale geared toward fashion-related brands.